Perencanaan Strategis SI/TI Menggunakan Analisis Ward & Peppard Pada Toko Trubus Pekabaru - Aryanto; Edo Arribe; Tengku Muhammad Zainul Aprilizar (Computer Science and Information Technology, 2023)
Toko Trubus is a company that wants to invest in IS in the form of software development for its strategic business needs by using outsourcing services. Using information systems and information technology can improve business strategy. This analysis is useful for designing IS/IT that produces the output of a portfolio of software applications that best suit the conditions or needs of the company in achieving goals based on the vision and mission. Therefore, research using the Ward & Peppard method is expected to obtain optimal results in accordance with the objectives of this company's business strategy. It is hoped that this framework can improve the company's management process by managing information better in the future. This Ward & Peppard methodology is a methodology in which there are several diagrams that will help how to understand an organization or company, with an IS/IT strategic plan, so that it has an impact on future plans.